Drying strategy of a rotary drum longan dryer - Thararux C. (2014)
A batch type rotary drum longan dryer is studied in this research work. A mathematical model for dehydration of whole longans to determine appropriate operating conditions of the dryer has been developed. The parameters affecting the drying performances are the drying air temperature, the airflow rate and the drum rotational speed. The experimental results agree very well with those of the simulated values. It is found that the appropriate operating condition is achieved when the drum rotational speed is 0.75 rpm. The drying air temperature is about 95°C when the specific mass flow rate of air is less than about 4.3 kg/h-kg dried longan and when the value is over this, the drying temperature should be 75°C.